Lightweight composite foam concrete and preparation method thereof
By using porous shale ceratops and layered organic bentonite in lightweight composite foam concrete, the moisture diffusion path is extended, and the volume shrinkage problem caused by excessive moisture evaporation is solved, and the mechanical properties and permeability of the product are significantly improved.
Patent Information
- Application Number
- CN202411410552.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-10
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
During the curing process, lightweight composite foam concrete shrinks and cracks the material volume due to excessive moisture evaporation, affecting its mechanical properties and anti-seepage properties.
Porous shale ceratops as aggregates, combined with large and small-grain layered organic bentonite, through ultrasonic dispersion and embedded with different mass cetyl trimethyl ammonium bromide, extending the water diffusion path and slowing down moisture evaporation Rate, reduce material volume shrinkage.
It effectively controls the water evaporation rate, reduces material volume shrinkage and cracking, and improves the compressive strength and water resistance of the product.
Smart Images

Figure BDA0005077862230000081 
Figure BDA0005077862230000091
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of building materials, and more specifically, relates to a lightweight composite foam concrete and a preparation method thereof. Background Art
[0002] Lightweight composite foam concrete is a lightweight porous concrete material made by mixing cement, water, foaming agent and other materials in a certain proportion, introducing bubbles through physical or chemical methods, and then mixing, pouring, molding and curing.
[0003] It has the following characteristics: lightweight. Due to the large number of closed pores inside, the density of lightweight composite foam concrete is low, which can reduce the weight of the building. It is often used in roofs, walls and other parts to reduce structural loads; thermal insulation. The closed pore structure gives it good thermal insulation properties and is suitable for energy-saving requirements of buildings; good seismic resistance. Due to its light weight, lightweight composite foam concrete is subject to less impact in natural disasters such as earthquakes and has good seismic resistance.
[0004] During construction, the following steps are usually included: raw material preparation, including cement, water, foaming agent, etc.; mixing the raw materials according to the designed ratio; using special equipment to stir the materials and introduce bubbles; pouring the stirred foam concrete slurry into the formwork; and curing until the designed strength is reached.
[0005] However, during the curing process of foam concrete, the humidity control is relatively strict. If the humidity is not properly controlled, it is easy to cause the foam concrete surface to lose water too quickly. Due to the rapid evaporation of water, the material may shrink in volume, causing cracks, and ultimately affecting product performance. Summary of the invention
[0006] The technical problem to be solved by the present invention is: for the existing lightweight composite foam concrete system, during the curing process, it is easy for the water to evaporate too quickly, resulting in the shrinkage of the material volume, thereby causing cracking, affecting the final mechanical properties or anti-seepage properties of the product. The present invention provides a lightweight composite foam concrete and a preparation method thereof.
[0007] The purpose of the invention is to provide a lightweight composite foam concrete.
[0008] Another object of the present invention is to provide a method for preparing lightweight composite foam concrete.
[0009] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0010] A lightweight composite foam concrete comprises the following raw materials in parts by weight:
[0011] 120-130 parts shale ceramsite
[0012] 15-20 parts of large-particle layered organic bentonite
[0013] 12-16 parts small particle layered organic bentonite
[0014] 300-320 parts of cement
[0015] 30-35 parts of foaming agent
[0016] 4-6 parts of foam stabilizer
[0017] 10-15 parts water reducing agent
[0018] The water-cement ratio of the lightweight composite foam concrete is 0.45-0.55;
[0019] The D50 of the shale ceramsite is 20-25 mm;
[0020] The shale ceramsite is porous ceramsite, the density of the porous ceramsite is 1400-1500 kg / m3, and the average pore size of the porous ceramsite is 0.6-0.8 mm;
[0021] The D50 of the large-particle layered organic bentonite is 1.5-2.0 mm;
[0022] The D50 of the small-particle layered organic bentonite is 0.1-0.12 mm;
[0023] The large-particle layered organic bentonite is at least partially coated on the surface of the shale ceramsite and covers at least part of the pores on the surface of the shale ceramsite;
[0024] The small-particle layered organic bentonite is at least partially filled in the interior of the shale ceramsite and is filled in at least part of the pores in the interior of the shale ceramsite.
[0025] The above technical solution first introduces lightweight shale ceramsite as aggregate in the lightweight foam concrete system. On the one hand, the pores inside and on the surface of the shale aggregate can absorb and store water, thereby gradually releasing water during the concrete curing process to avoid excessive evaporation of water. At the same time, it can also play a supporting role and reduce the volume shrinkage of the material.
[0026] However, the inventors found that although the evaporation rate of water was controlled to a certain extent, shrinkage cracks were still prone to occur in local areas. Therefore, on the basis of the above, large and small layered organic bentonite were introduced. The reason for the layered organic bentonite is that the layered structure can effectively extend the diffusion path of water during the disordered accumulation process in the concrete system, thereby reducing the evaporation rate of water. In addition, after some organic bentonite is free, it is easy to distribute on the surface of the foam liquid film, thereby improving the strength of the liquid film and increasing the diffusion path of water on the surface of the liquid film. Most importantly, some large-particle organic bentonite can only be adsorbed and fixed on its surface because its particle size is larger than the pore size of shale ceramsite, and partially blocks its pores, thereby increasing the difficulty of water inside the pores to diffuse to the outside, thereby further slowing down the evaporation rate of water. The small-particle organic bentonite filled in the internal pores regulates the water diffusion path inside the pores and plays a supporting effect inside the pores, further reducing the volume shrinkage of the material.
[0027] Furthermore, the cement is selected from any one of 42.5# ordinary Portland cement and 52.5# ordinary Portland cement.
[0028] Furthermore, the foaming agent is selected from any one of sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, α-sulfo fatty acid methyl ester, and sodium lauryl sulfate.
[0029] Furthermore, the foam stabilizer is selected from any one of gelatin, glycerol, carboxymethyl cellulose, silicone oil, triethanolamine or gum arabic.
[0030] Furthermore, the water reducer is selected from any one of a lignin sulfonate water reducer, a melamine water reducer, an aminosulfonate water reducer, and a polycarboxylic acid water reducer.
[0031] Furthermore, hexadecyltrimethylammonium bromide is embedded between the layers of the large-particle layered organic bentonite, and the content of the hexadecyltrimethylammonium bromide is 10-12% of the mass of the large-particle organic bentonite;
[0032] Cetyltrimethylammonium bromide is embedded between the layers of the small-particle layered organic bentonite, and the content of the cetyltrimethylammonium bromide is 3-5% of the mass of the large-particle organic bentonite.
[0033] By embedding different masses of hexadecyltrimethylammonium bromide between the layers of large-particle and small-particle organic bentonite, for large-particle organic bentonite, more is embedded between the layers, and the interlayer spacing is relatively wider. The wider interlayer spacing makes the material have a lower density and is easy to be stripped and adsorbed on the surface of shale ceramsite under the action of ultrasound. The small-particle layered organic bentonite with less interlayer embedding has a relatively high density and is more difficult to strip under the action of ultrasound. Therefore, it is easier to diffuse and fill the pores inside the shale particles.
[0034] Furthermore, a silane coupling agent is adsorbed on the surface of the shale ceramsite, and the content of the silane coupling agent is 1-2% of the mass of the shale ceramsite;
[0035] The silane coupling agent is selected from any one of silane coupling agent KH-550, silane coupling agent KH-560 and silane coupling agent KH-570.
[0036] A method for preparing lightweight composite foam concrete, the specific preparation steps comprising:
[0037] Raw material preparation: weigh each component according to the raw material composition;
[0038] The shale ceramsite, large-particle layered organic bentonite and small-particle layered organic bentonite are mixed and dispersed in water, and after being uniformly dispersed by ultrasonication, the mixture is allowed to stand, filtered and dried to obtain a pretreated aggregate;
[0039] After cement and water are stirred and mixed, pre-treated aggregate and water reducing agent are added, and stirring and mixing are continued to be uniform to obtain pre-mixed slurry;
[0040] The foaming agent and the foam stabilizer are mixed with water and placed in the foaming agent for foaming to obtain a foaming liquid. The foaming liquid is then poured into the premixed slurry and mixed evenly to obtain a lightweight composite foam concrete. DETAILED DESCRIPTION
[0041] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0042] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0043] Example 1
[0044] Weigh and prepare the raw materials according to the following composition:
[0045] 120 parts shale ceramsite
[0046] 15 parts large particle layered organic bentonite
[0047] 12 parts small particle layered organic bentonite
[0048] 300 parts cement
[0049] 30 parts foaming agent
[0050] 4 parts foam stabilizer
[0051] 10 parts water reducing agent
[0052] The D50 of the shale ceramsite is 20 mm;
[0053] The shale ceramsite is porous ceramsite, and the density of the porous ceramsite is 1400kg / m 3 , and the average pore size of the porous ceramsite is 0.6 mm;
[0054] The D50 of the large-particle layered organic bentonite is 1.5 mm;
[0055] The D50 of the small-particle layered organic bentonite is 0.1 mm;
[0056] The cement is selected from any one of 42.5# ordinary Portland cement;
[0057] The foaming agent is selected from sodium dodecylbenzene sulfonate;
[0058] The foam stabilizer is selected from gelatin;
[0059] The water reducing agent is selected from lignin sulfonate water reducing agent;
[0060] Cetyltrimethylammonium bromide is embedded between the layers of the large-particle layered organic bentonite, and the content of the cetyltrimethylammonium bromide is 10% of the mass of the large-particle organic bentonite;
[0061] Cetyl trimethyl ammonium bromide is embedded between the layers of the small-particle layered organic bentonite, and the content of the cetyl trimethyl ammonium bromide is 3% of the mass of the large-particle organic bentonite;
[0062] The surface of the shale ceramsite is adsorbed with a silane coupling agent, and the content of the silane coupling agent is 1% of the mass of the shale ceramsite;
[0063] The silane coupling agent is selected from silane coupling agent KH-550;
[0064] The shale ceramsite, large-particle layered organic bentonite and small-particle layered organic bentonite are mixed and dispersed in water, and ultrasonically dispersed for 40 minutes under an ultrasonic frequency of 180 kHz, and then allowed to stand at room temperature for 8 hours, filtered, and dried at a temperature of 100° C. to constant weight to obtain a pretreated aggregate;
[0065] In the above-mentioned processing process of the pretreated aggregate, the large-particle layered organic bentonite is at least partially coated on the surface of the shale ceramsite and covers at least part of the pores on the surface of the shale ceramsite;
[0066] The small-particle layered organic bentonite is at least partially filled in the shale ceramsite and at least partially filled in the pores in the shale ceramsite;
[0067] Cement and water were stirred and mixed with a stirrer at a speed of 180 r / min for 30 min, and then pretreated aggregate and water reducing agent were added, and the stirring and mixing was continued for 20 min to obtain a premixed slurry;
[0068] The foaming agent and the foam stabilizer are mixed with water and placed in the foaming agent for foaming to obtain a foaming liquid, and then the foaming liquid is poured into the premixed slurry, and the mixture is stirred and mixed with a stirrer for 30 minutes to obtain a lightweight composite foam concrete;
[0069] Wherein, the water-cement ratio of the lightweight composite foam concrete is 0.45.
[0070] Example 2
[0071] Weigh and prepare the raw materials according to the following composition:
[0072] 125 parts shale ceramsite
[0073] 18 parts large particle layered organic bentonite
[0074] 14 parts small particle layered organic bentonite
[0075] 310 parts cement
[0076] 32 parts foaming agent
[0077] 5 parts foam stabilizer
[0078] 12 parts water reducing agent
[0079] The D50 of the shale ceramsite is 22 mm;
[0080] The shale ceramsite is porous ceramsite, and the density of the porous ceramsite is 1450kg / m 3 , and the average pore size of the porous ceramsite is 0.7 mm;
[0081] The D50 of the large-particle layered organic bentonite is 1.8 mm;
[0082] The D50 of the small-particle layered organic bentonite is 0.11 mm;
[0083] The cement is selected from 42.5# ordinary Portland cement;
[0084] The foaming agent is selected from sodium lauryl sulfate;
[0085] The foam stabilizer is selected from carboxymethyl cellulose;
[0086] The water reducing agent is selected from melamine-based water reducing agents;
[0087] Cetyltrimethylammonium bromide is embedded between the layers of the large-particle layered organic bentonite, and the content of the cetyltrimethylammonium bromide is 11% of the mass of the large-particle organic bentonite;
[0088] Cetyltrimethylammonium bromide is embedded between the layers of the small-particle layered organic bentonite, and the content of the cetyltrimethylammonium bromide is 4% of the mass of the large-particle organic bentonite;
[0089] The surface of the shale ceramsite is adsorbed with a silane coupling agent, and the content of the silane coupling agent is 1.5% of the mass of the shale ceramsite;
[0090] The silane coupling agent is selected from silane coupling agent KH-560;
[0091] The shale ceramsite, large-particle layered organic bentonite and small-particle layered organic bentonite are mixed and dispersed in water, and ultrasonically dispersed for 42 minutes under an ultrasonic frequency of 190 kHz, and then allowed to stand at room temperature for 8 hours, filtered, and dried at a temperature of 100° C. to constant weight to obtain a pretreated aggregate;
[0092] In the above-mentioned processing process of the pretreated aggregate, the large-particle layered organic bentonite is at least partially coated on the surface of the shale ceramsite and covers at least part of the pores on the surface of the shale ceramsite;
[0093] The small-particle layered organic bentonite is at least partially filled in the shale ceramsite and at least partially filled in the pores in the shale ceramsite;
[0094] Cement and water were stirred and mixed with a stirrer at a speed of 180 r / min for 30 min, and then pretreated aggregate and water reducing agent were added, and the stirring and mixing was continued for 20 min to obtain a premixed slurry;
[0095] The foaming agent and the foam stabilizer are mixed with water and placed in the foaming agent for foaming to obtain a foaming liquid, and then the foaming liquid is poured into the premixed slurry, and the mixture is stirred and mixed with a stirrer for 30 minutes to obtain a lightweight composite foam concrete;
[0096] Wherein, the water-cement ratio of the lightweight composite foam concrete is 0.5.
[0097] Example 3
[0098] Weigh and prepare the raw materials according to the following composition:
[0099] 130 parts shale ceramsite
[0100] 20 parts large particle layered organic bentonite
[0101] 16 parts small particle layered organic bentonite
[0102] 320 parts cement
[0103] 35 parts foaming agent
[0104] 6 parts foam stabilizer
[0105] 15 parts water reducing agent
[0106] The D50 of the shale ceramsite is 25 mm;
[0107] The shale ceramsite is porous ceramsite, and the density of the porous ceramsite is 1500kg / m 3 , and the average pore size of the porous ceramsite is 0.8 mm;
[0108] The D50 of the large-particle layered organic bentonite is 2.0 mm;
[0109] The D50 of the small-particle layered organic bentonite is 0.12 mm;
[0110] The cement is selected from 42.5# ordinary Portland cement;
[0111] The foaming agent is selected from α-sulfo fatty acid methyl ester;
[0112] The foam stabilizer is selected from gum arabic;
[0113] The water reducing agent is selected from polycarboxylic acid water reducing agent;
[0114] Cetyltrimethylammonium bromide is embedded between the layers of the large-particle layered organic bentonite, and the content of the cetyltrimethylammonium bromide is 12% of the mass of the large-particle organic bentonite;
[0115] Cetyltrimethylammonium bromide is embedded between the layers of the small-particle layered organic bentonite, and the content of the cetyltrimethylammonium bromide is 5% of the mass of the large-particle organic bentonite;
[0116] The surface of the shale ceramsite is adsorbed with a silane coupling agent, and the content of the silane coupling agent is 2% of the mass of the shale ceramsite;
[0117] The silane coupling agent is selected from silane coupling agent KH-570;
[0118] The shale ceramsite, large-particle layered organic bentonite and small-particle layered organic bentonite are mixed and dispersed in water, and ultrasonically dispersed for 45 minutes under an ultrasonic frequency of 200 kHz, and then allowed to stand at room temperature for 8 hours, filtered, and dried at a temperature of 100° C. to constant weight to obtain a pretreated aggregate;
[0119] In the above-mentioned processing process of the pretreated aggregate, the large-particle layered organic bentonite is at least partially coated on the surface of the shale ceramsite and covers at least part of the pores on the surface of the shale ceramsite;
[0120] The small-particle layered organic bentonite is at least partially filled in the shale ceramsite and at least partially filled in the pores in the shale ceramsite;
[0121] Cement and water were stirred and mixed with a stirrer at a speed of 180 r / min for 30 min, and then pretreated aggregate and water reducing agent were added, and the stirring and mixing was continued for 20 min to obtain a premixed slurry;
[0122] The foaming agent and the foam stabilizer are mixed with water and placed in the foaming agent for foaming to obtain a foaming liquid, and then the foaming liquid is poured into the premixed slurry, and the mixture is stirred and mixed with a stirrer for 30 minutes to obtain a lightweight composite foam concrete;
[0123] Wherein, the water-cement ratio of the lightweight composite foam concrete is 0.55.
[0124] Example 4
[0125] The difference between this embodiment and embodiment 1 is that hexadecyl trimethyl ammonium bromide is embedded between the layers of the large-particle layered organic bentonite, and the content of the hexadecyl trimethyl ammonium bromide is 8% of the mass of the large-particle organic bentonite. The other conditions remain unchanged.
[0126] Example 5
[0127] The present embodiment is different from the embodiment 1 in that hexadecyltrimethylammonium bromide is embedded between the layers of the small-particle layered organic bentonite, and the content of the hexadecyltrimethylammonium bromide is 7% of the mass of the large-particle organic bentonite, and the other conditions remain unchanged.
[0128] Comparative Example 1
[0129] The difference between this comparative example and Example 1 is that no large-particle layered organic bentonite is added, and other conditions remain unchanged.
[0130] Comparative Example 2
[0131] The difference between this comparative example and Example 1 is that no small particle layered organic bentonite is added, and other conditions remain unchanged.
[0132] Comparative Example 3
[0133] The difference between this comparative example and Example 1 is that no large-particle layered organic bentonite and small-particle layered organic bentonite are added, and other conditions remain unchanged.
[0134] The performance tests were performed on the products obtained in the above examples and comparative examples. The specific test methods and test results are as follows:
[0135] The products obtained in the above-mentioned examples and comparative examples were poured into a template, and then left to stand for 28 days at a temperature of 25° C. and a relative humidity of 65%, and then demolded to obtain a concrete test block;
[0136] According to the provisions of "Foamed Concrete" (JG / T266-2011), the compressive strength of the above concrete test blocks was tested to obtain a compressive strength of 1;
[0137] After the concrete test block is immersed in water for 8 hours, it is taken out and drained, and the compressive strength after immersion is tested according to the above standard to obtain the compressive strength 2;
[0138] Please see Table 1 for specific test results;
[0139] Table 1: Product performance test results
[0140]
[0141]
[0142] It can be seen from the test results in Table 1 that the product obtained by the present invention has good compressive strength and excellent mechanical properties. In addition, due to the small number of surface cracks, it has excellent water resistance and the compressive strength does not decrease significantly after long-term immersion.
[0143] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A lightweight composite foam concrete, characterized in that: The invention comprises the following raw materials in parts by weight: 120-130 parts shale ceramsite 15-20 parts of large-particle layered organic bentonite 12-16 parts small particle layered organic bentonite 300-320 parts of cement 30-35 parts of foaming agent 4-6 parts of foam stabilizer 10-15 parts water reducing agent The water-cement ratio of the lightweight composite foam concrete is 0.45-0.55; The D50 of the shale ceramsite is 20-25 mm; The shale ceramsite is porous ceramsite, and the density of the porous ceramsite is 1400-1500kg / m 3 , and the average pore size of the porous ceramsite is 0.6-0.8mm; The D50 of the large-particle layered organic bentonite is 1.5-2.0 mm; The D50 of the small-particle layered organic bentonite is 0.1-0.12 mm; The large-particle layered organic bentonite is at least partially coated on the surface of the shale ceramsite and covers at least part of the pores on the surface of the shale ceramsite; The small-particle layered organic bentonite is at least partially filled in the interior of the shale ceramsite and is filled in at least part of the pores in the interior of the shale ceramsite.
2. A lightweight composite foam concrete according to claim 1, characterized in that: The cement is selected from any one of 42.5# ordinary Portland cement and 52.5# ordinary Portland cement.
3. A lightweight composite foam concrete according to claim 1, characterized in that: The foaming agent is selected from any one of sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, α-sulfo fatty acid methyl ester, and sodium lauryl sulfate.
4. A lightweight composite foam concrete according to claim 1, characterized in that: The foam stabilizer is selected from any one of gelatin, glycerol, carboxymethyl cellulose, silicone oil, triethanolamine or gum arabic.
5. The lightweight composite foam concrete according to claim 1, characterized in that: The water reducer is selected from any one of a lignin sulfonate water reducer, a melamine water reducer, an aminosulfonate water reducer, and a polycarboxylic acid water reducer.
6. A lightweight composite foam concrete according to claim 1, characterized in that: Cetyltrimethylammonium bromide is embedded between the layers of the large-particle layered organic bentonite, and the content of the cetyltrimethylammonium bromide is 10-12% of the mass of the large-particle organic bentonite; Cetyltrimethylammonium bromide is embedded between the layers of the small-particle layered organic bentonite, and the content of the cetyltrimethylammonium bromide is 3-5% of the mass of the large-particle organic bentonite.
7. A lightweight composite foam concrete according to claim 6, characterized in that: The surface of the shale ceramsite is adsorbed with a silane coupling agent, and the content of the silane coupling agent is 1-2% of the mass of the shale ceramsite; The silane coupling agent is selected from any one of silane coupling agent KH-550, silane coupling agent KH-560 and silane coupling agent KH-570.
8. A method for preparing the lightweight composite foamed concrete according to any one of claims 1 to 7, characterized in that: The specific preparation steps include: Raw material preparation: weigh each component according to the raw material composition; The shale ceramsite, large-particle layered organic bentonite and small-particle layered organic bentonite are mixed and dispersed in water, and after being uniformly dispersed by ultrasonication, the mixture is allowed to stand, filtered and dried to obtain a pretreated aggregate; After cement and water are stirred and mixed, pre-treated aggregate and water reducing agent are added, and stirring and mixing are continued to be uniform to obtain pre-mixed slurry; The foaming agent and the foam stabilizer are mixed with water and placed in the foaming agent for foaming to obtain a foaming liquid. The foaming liquid is then poured into the premixed slurry and mixed evenly to obtain a lightweight composite foam concrete.